Evaluation of Information Technology Based Online Learning Needs Assessment in Polytechnic in the Era of Covid-19 - Toyipur Toyipur (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
This research is a needs assessment evaluation which aims to determine the effectiveness of the information technology-based learning program, namely online or online learning to emphasize the difference between the desired or should be or expected conditions (what is) or real / real conditions. in the Covid-19 era with truth and validity data, facts, or information. The research was conducted using mixed methods research or a combination of qualitative and quantitative research in one study with evaluation of